RNA-Based Analysis Reveals High Diversity of Plant-Associated Active Fungi in the Atmosphere - Chen, Yan; Zhu, Xishen; Hou, Ziqiong; Wang, Yi; Zhou, Yunying; Wang, Ling; Liu, Lin; Duan, Jingrong; Jibril, Sauban Musa; Li, Chengyun (Frontiers in Microbiology, 2021)
Fungi are ubiquitous in nature; that is, they are present everywhere on the planet, understanding the active state and functional capacity of airborne microbes associated with health of human, animal and plant is critical for biosafety management. Here, we firstly and directly proved that there were about 40% active fungi in the air via rRNA amplicon sequencing and imaging flow cytometry simultaneously. Amplicon sequencing analysis showed differences between structures of active and total fungal community, Ascomycota were dominant in active community, while Basidiomycota have low transcriptional activity across all samples. Notably, plant pathogenic fungi were predominant in the air and more than 50% were active, including not only several common plant pathogens, but also biotrophic fungi (Erysiphe sp. and Microbotryum sp.) and host-specific pathogens which were generally considered to be inactive after leaving the host. Putative plant pathogens of eight genera were found active across the sampling season, indicating their superior ability to obtain nutrients even in barren nutrient environments. Interestingly, we detected several potentially active unrecorded fungi in China (Diatrype prominens, Septofusidium herbarum, Pseudomicrostroma glucosiphilum and Uromycladium tepperianum), suggested they spread over a long distance by air, and may cause diseases under favorable conditions. Our results suggested that maintain and transmission in air is essential feature of many fungi including plant pathogens regardless of being biotrophic, hemibiotrophic or necrotrophic group. Moreover, two potentially active human pathogens and one animal pathogens were captured indicated their potential risks. This study provided a new perspective for more comprehensive understanding of airborne fungi, including their multidimensional lifestyle, state, functioning and potential pathogenic risk. It also laid foundation for further prediction and management of airborne microbial communities that would be of interest for public health and agriculture.